Faktor-Faktor yang Mempengaruhi Penerapan Sasaran Keselamatan Pasien di Ruang Rawat Inap : (Studi Kasus pada Rumah Sakit Umum Daerah Ruteng Kabupaten Manggarai Propinsi NTT) - Fergilius Nardi Wa’os; Farida Yuliaty; Chevi Wirawan (Universitas Insan Budi Utomo, 2024)
This study aims to analyze the factors influencing the implementation of patient safety at RSUD Ruteng, Manggarai Regency, focusing on leadership, communication, teamwork, and human resources. The research employed a quantitative approach with a descriptive survey involving 70 respondents selected through purposive sampling. Data were collected using a Likert-scale questionnaire and analyzed using simple linear regression tests. The results indicated that leadership, communication, teamwork, and human resources significantly influenced the implementation of patient safety goals with a p-value < 0.05. These findings highlight the importance of a patient safety culture involving team collaboration, transformational leadership, and effective human resource management to improve hospital service quality.